PENGARUH PROFITABILITAS DAN INTENSITAS ASET TETAP TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG DAN KONSUMSI - Syawali, Pratami Eka Aulia (Jurnal Ilmu Akuntansi, 2023)
The purpose of this research is to determine the effect of profitability and fixed asset intensity on tax avoidance in manufacturing companies in the goods and consumption industry sector listed on the Indonesia Stock Exchange in 2019-2022. The population in this study, 84 Manufacturing Companies in the Goods and Consumption industry sector listed on the Indonesia Stock Exchange. The sample used in this study was 30 companies with 120 financial statement. The sample determination used non-probability sampling techniques with purposive sampling method. This research is a quantitative method with an associative approach, the data in this research was processed using SPSS with classic assumption test and multiple liniear regressions analysis. The measurement scale used in this study is a ratio scale. The result of this research shows that proportion of profitability has a significant influence on tax avoidance. Fixed asset intensity has a significant influence on tax avoidance. The contribution of the variable profitability and fixed asset intensitiy to the tax avoidance is 29,3%. Keywords: Profitability; Fixed Asset Intensity; Tax Avoidance